Evaluation of the quality of fruits and coconut water of different cultivars (Research, Society and Development, 2020)
Coconut is a fruit of great economic importance. Coconut water is used as a natural rehydrator, energy drink and helps in the treatment of various health problems. However, its quality may change during the development of the fruit. The objective was to evaluate the quality of fruits and coconut water of four cultivars. Coconuts from the cultivars Anã Amarela (AA), Anã Vermelho (AVE), Anã Verde (AVO) and Coco Híbrido (CH) were harvested, sanitized and drilled for water extraction. The transverse and longitudinal diameters and the water volume of the fruits were quantified. The contents of total soluble solids, total titratable acidity, pH, ratio, minerals (calcium, manganese, zinc, iron and copper) and electrical conductivity of the water were evaluated. The physical characteristics of the coconuts and the physico-chemical characteristics of the water were similar due to the standardization in cultivation and harvesting. The quality of coconuts in cultivars AA, AVE, AVO and CH did not vary significantly at seven months of age.